Deciphering nitrogen-driven microbial succession in an anaerobic membrane bioreactor-coupled A2/O ecological system for the remediation of industrial swine wastewater - Jing Huang; Feilong Wu; Yanchun Xiao; Meifeng Ye; Xiaomei Wu; Han Chen; Qingxian Xu (Scientific Reports)
Abstract Rapid expansion of industrial pig farming has intensified existing challenges in the management of nutrient-rich wastewater, characterized by high organic loads (chemical oxygen demand (COD): 15,000–30,000 mg/L) and ammonium nitrogen (NH4 +-N): 800–2,500 mg/L) concentrations. In this study, an integrated treatment system with a combination of a high-density polyethylene (HDPE) membrane-based anaerobic membrane bioreactor and an anoxic/aerobic/oxidation pond (A2/O) was developed for swine wastewater remediation. The system achieved exceptional remediation efficiency, removing 99.4, 99.5, 95.4, 92.8, and 97.9% of COD, biochemical oxygen demand (BOD), NH4 +-N, total phosphorus (TP), and suspended solids (SS), respectively, with the anoxic and aerobic (A2) phases contributing to removal of 62.5, 60.9, 80.9, 94.6% of COD, BOD, TP, and SS, respectively. Microbial community analysis revealed process-specific dynamics, including Firmicutes enrichment (8.52 ± 3.33 to 10.81 ± 0.39%) in anaerobic stages and Nitrosomonas dominance (2.38 ± 0.21%) during nitrification. The HDPE membrane-based bioreactor performed effectively under high organic loading rates (5–8 kg COD·m–3·day–1), whereas the A2/O system optimized nutrient cycling through synchronized nitrification-denitrification (dissolved oxygen: 2.0–3.5 mg/L). In this study, we establish a scalable framework for the treatment of industrial swine wastewater by combining engineered infrastructure with the principles of microbial ecology to address conventional pollutants.